(untitled) (Fiep Bulletin - online, 2014)
Considering the statistical crescents seriously regarding the patients burned, it was researched the procedures of First Aid to be accomplished in the emergency services to turn the effective service and based scientifically, and like this to increase the patient’s supervened. A bibliographical rising of the last 5 years was accomplished, by researches in books and published articles, which were organized as of research and of revision and later mentioned in agreement with the related statistics, the burned patient’s supervened and protocols of emergency service. It was ended that the team should be capable for: evaluation, determining the gravity, depth and the agent cause of the burn; First Aid, organizing the room in a functional and practical way, using technique and scientific knowledge; I handle of the wound and treatment. Being like this, it is noticed the need of service protocols, so that the work of the team is uniform and effective, guaranteeing the survival and preventing the patient’s complications seriously burned.